Effect of Light Acclimation on the Organization of Photosystem II Super- and Sub-Complexes in Arabidopsis thaliana - Bielczynski, Ludwik W.; Schansker, Gert; Croce, Roberta (Frontiers in Plant Science, 2016)
To survive under highly variable environmental conditions, higher plants have acquired a large variety of acclimation responses. Different strategies are used to cope with changes in light intensity with the common goal of modulating the functional antenna size of Photosystem II. Here we use a combination of biochemical and biophysical methods to study these changes in response to acclimation to high light. After two hours of exposure, a decrease in the amount of the large PSII supercomplexes is observed indicating that plants are already acclimating to high light at this stage. It is also shown that in high light the relative amount of antenna proteins decreases but this decrease is far less than the observed decrease of the functional antenna size, suggesting that part of the antenna present in the membranes in high light does not transfer energy efficiently to the reaction center. Finally, we observed LHCII monomers in all conditions. As the solubilization conditions used do not lead to monomerization of purified LHCII trimers, we should conclude that a population of LHCII monomers exists in the membrane. The relative amount of LHCII monomers strongly increases in plants acclimated to high light, while no changes in the trimer to monomer ratio are observed upon short exposure to stress.